Specific adaptations of patellar and Achilles tendons in male sprinters and endurance runners. Issue 3 (18th April 2018) - Ueno, H.; Suga, T.; Miyake, Y.; Takao, K.; Tanaka, T.; Misaki, J.; Otsuka, M.; Nagano, A.; Isaka, T.
Abstract : This study aimed to determine the impact of long‐term training on Achilles tendon (AT) and patellar tendon (PT) hypertrophy in sprinters and endurance runners. The cross‐sectional area (CSA) of AT and PT in 40 sprinters, 40 endurance runners, and 40 untrained subjects was measured using magnetic resonance imaging. The AT and PT CSAs were calculated at its proximal, middle, and distal portions. Three CSAs of AT and PT were averaged to give an overall absolute CSA for each tendon. To minimize the effect of body size on tendon CSA and obtain relative CSA, overall absolute CSA for each tendon was normalized with body mass. Absolute AT CSA did not differ significantly among all 3 groups. However, we found that relative AT CSA was significantly larger in endurance runners than in sprinters and untrained subjects ( P < .001 for both). In contrast, both absolute and relative PT CSAs were significantly larger in sprinters than in endurance runners and untrained subjects ( P ≤ .001 for all). These findings indicate that AT hypertrophy is characteristic of endurance runners, whereas PT hypertrophy is characteristic of sprinters. Therefore, we suggest that the AT and PT may undergo specific morphological adaptations in these athletes.